Taxonomy of the genus Osorius Guérin-Méneville (Coleoptera: Staphylinidae, Osoriinae) from China - Zou, Si-Si; Zhou, Hong-Zhang (Zootaxa, 2015)
This paper studies the taxonomy of the genus Osorius Guérin-Méneville, 1829 (Coleoptera: Staphylinidae, Osoriinae) and reports 10 new species and three new records from China: Osorius depressicapitatus sp. nov. (Yunnan and Xizang), O. guizhouensis sp. nov. (Guizhou), O. huangi sp. nov. (Hunan), O. limatidepressus sp. nov. (Sichuan), O. micromidas sp. nov. (Yunnan), O. minutoserratus sp. nov. (Yunnan), O. rectomarginatus sp. nov. (Yunnan, Guangxi, Hainan, Fujian, Guangdong and Xizang), O. striolatus sp. nov. (Hunan and Guangdong), O. trichinosis sp. nov. (Guizhou and Zhejiang), O. tuberocapitatus sp. nov. (Hubei), O. aspericeps Fauvel, 1905, new record of China (Yunnan, Sichuan, Xizang and Zhejiang), O. frontalis Fauvel, 1905, new record of China (Sichuan), and O. punctulatus Motschulsky, 1857, new record of China (Yunnan and Fujian). The number of the Chinese Osorius species is thus increased to 21 in total. The paper provides line drawings for 21 species and redescriptions for the species recorded for the first time in China. A key to Chinese species is also included.